2008
DOI: 10.1029/2007wr006224
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic description of grain resistance from simultaneous flow field and grain motion measurements

Abstract: [1] Experiments were carried out using a mobile gravel bed placed in a tilting flume with a modified particle image velocimetry (PIV) system. Individual grain movements were surveyed using data from time series of images. Near-bed velocity flow field measurements were made simultaneously above the same area of the sediment surface by applying cross-correlation techniques to the collected plan view images. Statistics of grain motions were collected through a semiautomatic procedure. Significant changes in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
(43 reference statements)
1
24
0
Order By: Relevance
“…Visually, it is diffi cult to assess if transport events coincide with high or low values of any of the seven variables. This attests to the fact that there are no unique sets of conditions under which particle are mobilized as observed by Bottacin-Busolin et al (2008). The following observations can be made: (1) transport events occur both at high or low streamwise velocity; (2) many transport events occur concomitantly to a positive vertical velocity; (3) high Reynolds shear stress values do not seem to be associated with transport events; (4) several transport events coincide with peaks in the streamwise and vertical normal stresses; (5) most events occur at rapid transitions in the streamwise and vertical fl ow velocities, thus hinting at the potential role of fl uid acceleration and deceleration on the bedload movement.…”
Section: Linking Mean and Turbulent Fl Ow Variables With Individual Tmentioning
confidence: 72%
“…Visually, it is diffi cult to assess if transport events coincide with high or low values of any of the seven variables. This attests to the fact that there are no unique sets of conditions under which particle are mobilized as observed by Bottacin-Busolin et al (2008). The following observations can be made: (1) transport events occur both at high or low streamwise velocity; (2) many transport events occur concomitantly to a positive vertical velocity; (3) high Reynolds shear stress values do not seem to be associated with transport events; (4) several transport events coincide with peaks in the streamwise and vertical normal stresses; (5) most events occur at rapid transitions in the streamwise and vertical fl ow velocities, thus hinting at the potential role of fl uid acceleration and deceleration on the bedload movement.…”
Section: Linking Mean and Turbulent Fl Ow Variables With Individual Tmentioning
confidence: 72%
“…It has been demonstrated by others that some aspect of streamwise velocity strongly correlates with sediment entrainment transport, but that the cross products of velocity have a poorer relationship with sediment entrainment (Williams et al, 1989;Nelson et al, 1995;Papanicolaou et al, 2001;Schmeeckle and Nelson, 2003). For example, Bottacin-Busolin et al (2008) discovered that over half of the grain movements observed over a gravel bed were due to variations in the streamwise component of velocity, and only in a relatively small percentage of the cases (around one-tenth) were they characterised by changes in the cross-product of temporal fl uctuations in velocity. In simple terms, entrainment appears .…”
Section: Contributions To the Total Fluid Forcementioning
confidence: 96%
“…Bottacin-Busolin et al (2008) performed measurements at a level of shear stress just above the critical shear stress, so they were only able to characterise the lower range of critical entrainment velocities. Instead we have simulated the distribution of τ c using a discrete particle model first developed by McEwan and Heald (2001).…”
Section: Estimation Of Critical Shear Stressmentioning
confidence: 99%